Practices and attitudes towards disinformation activities among students of media classes at the Università di Parma – a preliminary study - Krysiński, Przemysław; Pamuła, Natalia; Conti, Giulia (Polityka i Społeczeństwo, 2025)
This article was created to turn attention to the practices and attitudes towards disinformation adopted by students of selected fields of study related to information and media, conducted at the Università di Parma. The research was conducted using a diagnostic survey method on a group of 120 people (research sample 60%). The students surveyed are everyday users of the Internet. A high percentage of respondents declared that they verify information from this communication channel, although a significant percentage of respondents do not pay attention to it, did not answer this question or clearly declared that they do not do so. For them, the factors influencing the credibility of information are a credible source, support from an authority and lack of bias in presenting facts. The students declare that they have encountered disinformation content. The most common examples of this include fake news, false visual and audiovisual content and trolling. According to the respondents, the main purpose of disinformation was to mislead public opinion motivated by various motives. A small percentage of respondents believe that disinformation can cause negative attitudes towards other nations. It is not surprising that a large part of the surveyed group has encountered disinformation about vaccinations or climate change. A significant percentage of recipients also encountered content related to the war in Ukraine, 5G technology, refugees, but also the flat earth theory, abortion and ethnic and national minorities. Students point to Russia as actors on the disinformation scene. It should also be noted that the United States, China and Israel received high ratings, while Italy received one of the lowest percentages. The respondents believe that the greatest threats from disinformation on the Internet are the destabilization of the political and social situation, while at the same time reducing national security, indicating it as one of the least threatening factors. 70% of them believe that it increases the abilities of recipients in the process of verifying information.